Papers of Michael Glas - Glas, Michael; Glas, Alice (1938)
MS Acc11.140 comprises correspondence between Alice and Michael Glas, while Michael was interned in Australia and Alice was interned on the Isle of Man, correspondence between Alice Glas and various authorities relating to Michael's internment, photographs and copies of letters possibly on printing-out paper (2 boxes).
Manuscript reference number: MS Acc11.140.
Michael Glas was an Austrian who served as a soldier for the German Kaiser in the First World War. In 1938, he travelled to England, following Alice (Liesl) Lichtblau, a young woman he had met while working in a bank in Austria. Michael and Alice were married in Islington, and a few months later he was arrested as an enemy alien and sent to a camp in Devonshire. Later, he was on board the Andorra Star being sent to Canada when the ship was torpedoed in the Irish sea and sank. The survivors, including Michael, were returned to Liverpool and subsequently sent to Australia on board HMT Dunera.
Some items in German.
Keywords: Glas, Michael -- Archives; Dunera (Ship); Prisoners of war -- Austria -- Archives; Prisoners of war -- Australia -- Archives; Austrians -- Australia -- Archives; Concentration camps -- Australia; World War, 1939-1945 -- Prisoners and prisons, Australian; Internees